2020
DOI: 10.3892/or.2020.7614
|View full text |Cite
|
Sign up to set email alerts
|

Sea cucumber Cucumaria frondosa fucoidan inhibits osteosarcoma adhesion and migration by regulating cytoskeleton remodeling

Abstract: Osteosarcoma (OS) has been demonstrated to be difficult to cure due to its potently malignant metastasis. Therefore, new therapeutic approaches blocking the metastatic potential of OS are urgently required to improve the outcomes for OS patients. In the present study, the anti-metastatic capacity of sea cucumber (Cucumaria frondosa) fucoidan (Cf-Fuc) was evaluated on osteosarcoma cells by cell adhesion assay, Transwell assay and U2OS cell migration assay. The underlying mechanism on the dynamic remodeling of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…These results are consistent with previous reports. Zhang reported that fucoidan inhibited osteosarcoma cell adhesion by suppression of the phosphorylation of FAK and paxillin ( Zhang et al, 2020 ). In addition, fucoidan suppressed mouse hepatocarcinoma Hca-F cells adhesion via downregulating L-selectin and upregulating protein levels of tissue inhibitor of metalloproteinases (TIMPs) ( Wang et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with previous reports. Zhang reported that fucoidan inhibited osteosarcoma cell adhesion by suppression of the phosphorylation of FAK and paxillin ( Zhang et al, 2020 ). In addition, fucoidan suppressed mouse hepatocarcinoma Hca-F cells adhesion via downregulating L-selectin and upregulating protein levels of tissue inhibitor of metalloproteinases (TIMPs) ( Wang et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fucoidan from the sea cucumber Cucumaria frondosa has been reported to inhibit in vitro migration of human osteosarcoma U2OS cells by impairing dynamic cytoskeletal remodeling through the suppression of the phosphorylation of FAK and paxillin and activation of the Rac1/PAK1/LIMK1/cofilin signaling axis [ 50 ].…”
Section: Marine Compounds As Migrastaticsmentioning
confidence: 99%
“…Yoshizawa and Coll demonstrated that 6-Hydroxythiobinupharidine isolated from Nuphar pumilum inhibits migration of LM8 OS cells by decreasing the expression of LIMK 1 [ 157 ]. More recently, Zhang and Coll showed that fucoidan from the sea cucumber Cucumaria frondosa inhibits OS adhesion and migration by regulating cytoskeleton remodelling via the Rac1/PAK1/LIMK1/cofilin signalling axis [ 158 ].…”
Section: Limks and Primary Bone Tumourmentioning
confidence: 99%